Patient satisfaction and uptake of private-sector run malaria diagnosis clinics in a post-conflict district in Sri Lanka - Fernando, Deepika (BioMed Central, 2014)
BACKGROUND: With the incidence of malaria in Sri Lanka declining, intensive parasitological surveillance has been identified as a key strategy to achieve elimination by end 2014. Tropical and Environmental Diseases and Health Associates Private Limited (TEDHA) in collaboration with the Anti-Malaria Campaign established 43 malaria diagnostic laboratories (MDL) in four post-conflict districts of the Northern and Eastern Provinces. This study assesses the patterns of referral of patients with fever for malaria diagnosis by health care providers (HCPs) in four government hospitals in one of the districts of the Northern Province, and patient satisfaction with the laboratory services offered. METHODS: In this prospective descriptive study, data was collected on the proportion of fever patients being referred by the HCP in hospitals for malaria screening, and the proportion thereof who underwent screening. An interviewer-administered questionnaire was also used to assess patient satisfaction among those attending MDL, which was graded on a scale of 0–4. RESULTS: Of patients presenting to the hospitals with fever, only 44.3% were referred for malaria screening; 81.7% of them underwent screening. Referral depended largely on the presence of a permanent staff HCP. Satisfaction levels were high, with 86.55% giving an overall rating of 4. Comfort within the laboratory was rated satisfactory in three of the four hospitals. CONCLUSIONS: This study demonstrates the success of a public-private partnership in the malaria control programme in Sri Lanka. Malaria is considered low on the differential diagnosis in patients with fever even in previously malaria-endemic areas, due to the declining incidence of malaria and the increase in other febrile illnesses in these areas during the recent past. Private sector run malaria diagnostic services provided free of charge within government hospitals are viable and effective, and had good patient satisfaction ratings. In a country on the brink of eliminating malaria, there should be further emphasis on ensuring that HCPs refer patients for malaria diagnosis, in order to prevent a resurgence of the disease.